2023
DOI: 10.3991/ijet.v18i04.34821
|View full text |Cite
|
Sign up to set email alerts
|

Information Technologies that Help Improve Academic Performance, A Review of the Literature

Abstract: Currently in the world the use of technology is increasing and even more so in the time of Covid-19, when digitization is vital, essentially in education, more technological tools are being used to improve academic performance and learning. The study that was carried out is a review of the scientific literature, 127 articles were collected from the different databases; IEEE Xplore, ScienceDirect, EBSCO, Scielo, and Scopus. Based on the inclusion and exclusion criteria of the systematization used, only 53 have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 41 publications
0
0
0
Order By: Relevance
“…Similarly, studies such as those referenced in [37][38][39] have found that educational innovation is crucial in the educational process. It has enabled students in the field of mathematics to achieve better results and a deeper understanding of the topics when taught in an innovative and participatory manner.…”
Section: Discussionmentioning
confidence: 94%
“…Similarly, studies such as those referenced in [37][38][39] have found that educational innovation is crucial in the educational process. It has enabled students in the field of mathematics to achieve better results and a deeper understanding of the topics when taught in an innovative and participatory manner.…”
Section: Discussionmentioning
confidence: 94%
“…In delving deeper into the subject, it is crucial to reference a range of authoritative works. [11] conducted a systematic review of AI applications in Latin American higher education, offering insights into regional challenges. [12] emphasizes the proactive use of AI for monitoring student performance.…”
Section: Introductionmentioning
confidence: 99%
“…These AI tools are being used to provide students with personalized instruction, immediate feedback, and targeted practice [8]. This can help students learn at a faster pace and better understand the concepts they are learning [9,10].…”
Section: Introductionmentioning
confidence: 99%